Quality and effectiveness in probation officers' reports to sentencers - Gelsthorpe, Loraine (The British journal of criminology, 1995)
Preparations to implement the 1991 Criminal Justice Act in England and Wales included a pilot study organized by the Home Office to assess the impact of introducing pre-sentence reports in a wider range of cases in the Crown Courts. This paper reports some findings from the study concerning the variable quality of probation officers' reports; the level of agreement between the researchers' assessments of quality and those made by sentencers in the Crown Courts; and the impact of low and high quality reports on the sentencing process